1991
DOI: 10.1172/jci115058
|View full text |Cite
|
Sign up to set email alerts
|

Arterial mechanical properties in dilated cardiomyopathy. Aging and the response to nitroprusside.

Abstract: The effects of aging on arterial mechanical properties and the response to nitroprusside were examined in 25 patients with dilated cardiomyopathy. High-fidelity pressures were recorded with a multisensor catheter. Pulse wave velocity was determined between two sensors in the thoracic aorta. Arterial compliance was determined by an analysis of the diastolic waveform and cardiac output.At baseline, despite a similar systemic vascular resistance, the pulsatile load (e.g., arterial compliance) and wave transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 27 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…No direct effect on aortic stiffness has been found for nitrates in older human adults. [55][56][57] In very carefully controlled experimental studies on animals, nitrates have shown no direct effect on aortic characteristic impedance, despite marked effect on peripheral muscular arteries. 58 In contrast to inefficacy on aortic stiffness, nitrates and other arterial dilators have marked effects on wave reflection and can virtually eliminate the late systolic augmentation Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…No direct effect on aortic stiffness has been found for nitrates in older human adults. [55][56][57] In very carefully controlled experimental studies on animals, nitrates have shown no direct effect on aortic characteristic impedance, despite marked effect on peripheral muscular arteries. 58 In contrast to inefficacy on aortic stiffness, nitrates and other arterial dilators have marked effects on wave reflection and can virtually eliminate the late systolic augmentation Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Passive reduction in distending pressure can reduce aortic stiffness to a modest degree [2,31], but although data to the contrary exist [2,32], vasodilator drugs generally appear to have little direct beneficial effect. In contrast, the indirect effects of arterial stiffness can be offset to a substantial degree through reduction of wave reflection with vasodilator drugs that act on peripheral arteries and arterioles [2,26] (Fig.…”
Section: Modification Of Arterial Stiffnessmentioning
confidence: 99%
“…These details are important because each of these factors can influence arterial mechanical properties. [31][32][33] In particular, arterial size (which correlates fairly tightly with measures such as height and forearm volume) is a major determinant of mechanical properties, such as compliance and PWV, 20 independent of vessel stiffness.…”
Section: Potential Limitationsmentioning
confidence: 99%